2016
DOI: 10.1088/1054-660x/26/8/084001
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed periodic laser excitation of upconversion luminescence for deep biotissue visualization

Abstract: Emission spectral properties and quantum efficiency of upconversion particles NaYF 4 , SrF 2 , LaF 3 , BaF 2 и CaF 2 , doped with rare earth ions pair Yb 3+ -Er 3+ were studied using continuous wave (CW) and pulsed periodic excitation modes in the near infrared (NIR) spectral range. Analysis of the obtained results showed that the intensity ratio of upconversion luminescence in green and red spectral ranges depends on excitation pulse duration. Thus, by changing the pulse duration the spectral properties of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Luminescent materials based on lanthanides ions -ranging from molecular complexes to inorganic phosphors -remain not only interesting from a scientific point of view but also relevant for many new applications. 1,2 These applications include optical nanoprobes for medical usage, [3][4][5][6][7] colour conversion materials for light emitting diods, 8,9 organic light emitting diodes, 10 solar radiation converters, [11][12][13] luminescent thermometers [14][15][16][17] as well as inks used for anti-counterfeiting purposes. 18,19 In general, luminescence of lanthanide-based materials can be divided into two main types: Stokes and anti-Stokes.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials based on lanthanides ions -ranging from molecular complexes to inorganic phosphors -remain not only interesting from a scientific point of view but also relevant for many new applications. 1,2 These applications include optical nanoprobes for medical usage, [3][4][5][6][7] colour conversion materials for light emitting diods, 8,9 organic light emitting diodes, 10 solar radiation converters, [11][12][13] luminescent thermometers [14][15][16][17] as well as inks used for anti-counterfeiting purposes. 18,19 In general, luminescence of lanthanide-based materials can be divided into two main types: Stokes and anti-Stokes.…”
Section: Introductionmentioning
confidence: 99%
“…Liu’s group reported that the emission color of NaYF 4 :Nd/Yb@NaYF 4 :Yb/Tm@NaYF 4 @NaYF 4 :Yb/Ho/Ce@NaYF 4 core-multishell nanoparticles could change from green to red by prolonging pump pulse duration of a single-wavelength laser diode 11 . Then researchers found that the fluorescence green-to-red ratio (GRR) depends on the pulsed excitation and the crystal with a higher phonon energy is more sensitive to the pulsed duration 12 . Beyond the tunable emission color or peak ratio resulted from controlling pulse duration, the pulsed laser excitation brings about higher quantum yield than continuous-wave (CW) laser with equivalent average power density, enabling deep tissue optical bioimaging 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, color tunability of upconverted emission in a fixed material has always been a formidable challenge. Therefore, several studies were reported on non-steady-state excitation of UC nanoparticles to obtain color-tunable emission from a fixed material in various hosts. , Studies related to color tuning of UC materials by excitation modulation were mostly concentrated on lanthanide-doped NaYF 4 nanocrystals and applications ran through their direct uses as aqueous solutions or as nanocrystal-embedded polymer-based hosts. ,,, Additionally, there also exist several fundamental studies in some bulky crystalline hosts. However, to the best of our knowledge, there is no such study on the tuning of relative intensities of emission bands in lanthanide-doped glasses by excitation modulation. Tuning of emission colors in a fixed oxide glass composition doped with lanthanide ions can give rise to new possibilities and also may promote the already existing applications due to their favorable properties over crystalline and solution-based hosts .…”
Section: Introductionmentioning
confidence: 99%
“…11,13−16 Studies related to color tuning of UC materials by excitation modulation were mostly concentrated on lanthanide-doped NaYF 4 nanocrystals and applications ran through their direct uses as aqueous solutions or as nanocrystal-embedded polymer-based hosts. 10,11,13,17 Additionally, there also exist several fundamental studies in some bulky crystalline hosts. 14−16 However, to the best of our knowledge, there is no such study on the tuning of relative intensities of emission bands in lanthanide-doped glasses by excitation modulation.…”
Section: Introductionmentioning
confidence: 99%